2013
DOI: 10.1007/s10529-013-1229-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea

Abstract: Antifungalmycin 702, a novel polyene macrolide antibiotic produced by Streptomyces padanus JAU4234, strongly inhibited mycelial growth of the rice blast fungus, Magnaporthe grisea, with EC50 of 37 μg/ml and EC90 of 136 μg/ml. Significant reduction in the number of conidia was observed at above 20 μg/ml. Conidia germination and appressorium formation were also suppressed and were not viable with >40 μg/ml. When treated with antifungalmycin 702, hyphae morphology became irregular. Based on microscopic examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…These distorted hyphae had a flattened appearance. Similar conclusions have also been made in previous studies by Maoz and Neeman [25], and Xiong et al [26], who also found that hyphae morphology becomes irregular under certain treatment conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These distorted hyphae had a flattened appearance. Similar conclusions have also been made in previous studies by Maoz and Neeman [25], and Xiong et al [26], who also found that hyphae morphology becomes irregular under certain treatment conditions.…”
Section: Resultssupporting
confidence: 91%
“…These phenomena that were observed agree with Arlorio et al [27], who observed the rupture of fungal cell walls upon exposure to citral. These phenomena are likely due to the structure of citral, because the effects of solutes on cell walls might be influenced by compounds that possess a hydrophilic group and an electron acceptor group, such as an aldehyde group [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…The genus Streptomyces strains have antagonistic activity against wide range of phytopathogens. Concerning rice blast, S. canus BYB02, S. padanus JAU4234 and S. sindeneusis 263 strongly inhibited M. oryzae . The antifungal activity of S. endus was only reported in potato and zinnia with low efficiency .…”
Section: Discussionmentioning
confidence: 98%
“…MJM4426 showed biocontrol potential on rice bacterial blight . Antifungalmycin 702, a new polyene macrolide antibiotic from Streptomyces padanus JAU4234, suppressed rice blast pathogen . Resistomycin from Streptomyces canus BYB02 possessed significant preventive efficacy against rice blast .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al ( 2014 ) observed that the natural product citral caused damage to hyphal cell walls and membrane structures of P. grisea . The cell walls of P. grisea are strongly influenced by hydrophilic and aldehyde groups which damage or rupture cell walls and membranes (Xiong et al, 2013 ). A few studies also have shown that 2,4-DAPG plays an important role in the control of phytopathogens by damaging hyphal tips, causing vacuolization and cell content disintegration, and disrupting multiple basic cellular pathways including membrane function, reactive oxygen regulation, and cell homeostasis (de Souza et al, 2003 ; Kwak et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%